Wrong interpretation of the concept of «administration» and its influence on the efficiency of strategic management of territorial development (Economics and region, 2021)
The article defines the content of the concept of management function «administration». The existing methodological approaches to its understanding and implementation are generalized. The relationship between the concepts of regional development, strategy and administration is studied. The existence of erroneous and incomplete interpretation of the concept of administration and its negative impact on the strategic development of the region, according to which the main component of the function of administration is reduced to the implementation of management decisions, implementation of tasks. This ignores such an important component as strategy and strategic planning with the definition of goals, objectives and objectives. A new understanding of the studied definition is formulated, where the concept of administration is understood as a managerial system-situational communication process of making managerial decisions to organize effective collective work to develop, institutionalize and implement the goals, objectives and tasks (strategies and tactics) of the organization.
Keywords: management; administration; strategy; management functions; managerial decisions; regional development